Self-concept of grade 10 students with OFW parents as compared to students with non-ofw parents in De La Salle Araneta University - Aubrey C. Ortega. 4 0 16; 5 (2018)
ABSTRACT: This study wanted to find out if there is a significant difference between the levels of self-concept of grade 10 students with at least one parent working abroad as compared to grade 10 students who live with both their parents in De La Salle Araneta University. The researcher administered Piers-Harris Self-Concept 2 (The Way I Feel About Myself) to find out the levels of Overall Self-Concept, Behavioral Adjustment, Physical Appearance and Attributes, Intellectual and School Status, FDreedom from Anxiety, Popularity, and Happiness and Satisfaction. The sample size considered of 114 grade 10 students chosen by purposive sampling. The participants were described to have low average of self-concept. This study also found out that there is no significant difference between the self-concept of the children of OFW's and non-OFW's. Based on the results of this study, the researcher proposed a Homeroom Self-Concept Enhancement Program.
Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2